The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1113/jphysiol.2013.267872
|View full text |Cite
|
Sign up to set email alerts
|

Complementary functions of SK and Kv7/M potassium channels in excitability control and synaptic integration in rat hippocampal dentate granule cells

Abstract: Key pointsr Previous studies showed that different firing patterns of hippocampal dentate granule cells (DGCs) can trigger different network responses. However, the intrinsic DGC mechanisms controlling their excitability, spike patterns and synaptic integration in DGCs, remain poorly understood.r SK and Kv7/M channels play important roles controlling neuronal integration and excitability, but their specific roles vary between cell types. Both channel types are expressed in DGCs, but their roles are unclear.r W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 99 publications
(322 reference statements)
5
67
2
Order By: Relevance
“…However, previous studies have shown that in granule cells from epileptic tissue, the amplitude of low voltage–activated Ca 2+ currents was augmented, whereas the amplitude of I NaP was reportedly not increased . In addition, spike after‐hyperpolarizations are known to modulate firing pattern and excitability in granule cells . We found that the fAHP was reduced in the burst‐firing normotopic granule cells from epileptic animals, consistent with the type II granule cells found in epileptic tissue from patients .…”
Section: Discussionsupporting
confidence: 86%
“…However, previous studies have shown that in granule cells from epileptic tissue, the amplitude of low voltage–activated Ca 2+ currents was augmented, whereas the amplitude of I NaP was reportedly not increased . In addition, spike after‐hyperpolarizations are known to modulate firing pattern and excitability in granule cells . We found that the fAHP was reduced in the burst‐firing normotopic granule cells from epileptic animals, consistent with the type II granule cells found in epileptic tissue from patients .…”
Section: Discussionsupporting
confidence: 86%
“…However, this may not be of much importance. (Mateos-Aparicio et al 2014) found that k M values in the range 7-11 mV had little effect on the predictions of their dentate granule cell model. The relative error on V M (as estimated by V half ) was fairly small [ Fig.…”
Section: Effect Of Preserved Axon Length On Boltzmann Parameter Estimmentioning
confidence: 93%
“…However, it was necessary to set the time constant τ(V M ) = 1 s in eqn (7) to obtain a difference in V half comparable to the observed one (ß5 mV). This may be considered implausible for the one-component model described in the Methods, given the observed kinetics of g M activation and deactivation (Mateos-Aparicio et al 2014;Battefeld et al 2014). However, Mateos-Aparicio et al (2014) concluded that for a number of published studies the following two-component model gave a better description of g M kinetics:…”
Section: Effect Of Ramp 'Direction' On the Estimate Of V Halfmentioning
confidence: 99%
“…Channels contributing to the generation of mAHP are Kv7 channels as well as SK2 calcium-activated potassium channels and HCN channels [80,103,105]. However, it has been reported that distinct channels are responsible for mAHP depending on membrane potentials and neuronal types [104,106]. …”
Section: Kv7 Channel Physiologymentioning
confidence: 99%